EFEKTIVITAS BERBAGAI FORMULASI RIZOBAKTERI SEBAGAI BIOHERBISIDA PADA PERTANAMAN KEDELAI (Glycine max (L.) Merril) - Bahrawi, Afiati; Karimuna, La; Muhidin, Muhidin (Universitas Halu Oleo, 2018)
ABSTRACKThe purpose of this research was to study the effectiveness of various formulations rhizobacteria as bioherbicide in soybean. This research was conducted at the Agrotechnology Laboratory Unit Agronomy and Field Laboratory, Faculty of Agriculture Halu Oleo university, Kendari from March to June 2016.This research was arranged on randomized complete block design (CBD), which consisted of seven treatments that are P0 (Control), P1 (Bacillus sp. A05 + water), P2 (Bacillus sp. A05 + talc), P3 (Bacillus sp. A05 + husk charcoal powder), P4 (P. aeruginosa A08 + water), P5 (P. aeruginosa A08 + talc), P6 (P. aeruginosa A08 + husk charcoal powder). The treatments was repeated three times so that there were 21 experimental units. Weed vegetation were analyzed using quadratic metode, quadrant size used was 1x1 m2, observations were made one time when the soybean was 21 HST. The soybean data were analyzed using of analysis variance followed by Duncan's Multiple Range Test if the treatments was significant. The results showed that treatment of formulations rhizobacteria P6 namely P. aeruginosa A08 in the husk charcoal powder carrier formulation was the best among all 5 other formulations, that could be seen in the weeds vegetation analysis data results, showed that P. aeruginosa A08 in the husk charcoal powder carrier formulation could suppress the growth of Cleome rutidosperma D.C and Cyperus rotundus L. which was the dominant weeds in soybean. Husk charcoal powder was able to improve the suitability of rhizobacteria P. aeruginosa A08 as bioherbisida in the field so that they could worked more effectively as bioherbisida than other treatments. Keywords: Bioherbicides, formulation rhizobacteria, Glycine max (L.) Merrill